Development and assessment of the inter-rater and intra-rater reproducibility of a self-administration version of the ALSFRS-R. Issue 1 (26th September 2019) - Bakker, Leonhard A; Schröder, Carin D; Tan, Harold H G; Vugts, Simone M A G; van Eijk, Ruben P A; van Es, Michael A; Visser-Meily, Johanna M A; van den Berg, Leonard H
Abstract : Objective: The Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised (ALSFRS-R) is widely applied to assess disease severity and progression in patients with motor neuron disease (MND). The objective of the study is to assess the inter-rater and intra-rater reproducibility, i.e., the inter-rater and intra-rater reliability and agreement, of a self-administration version of the ALSFRS-R for use in apps, online platforms, clinical care and trials. Methods: The self-administration version of the ALSFRS-R was developed based on both patient and expert feedback. To assess the inter-rater reproducibility, 59 patients with MND filled out the ALSFRS-R online and were subsequently assessed on the ALSFRS-R by three raters. To assess the intra-rater reproducibility, patients were invited on two occasions to complete the ALSFRS-R online. Reliability was assessed with intraclass correlation coefficients, agreement was assessed with Bland-Altman plots and paired samples t -tests, and internal consistency was examined with Cronbach's coefficient alpha. Results: The self-administration version of the ALSFRS-R demonstrated excellent inter-rater and intra-rater reliability. The assessment of inter-rater agreement demonstrated small systematic differences between patients and raters and acceptable limits of agreement. The assessment of intra-rater agreement demonstrated no systematic changes between time points; limits of agreement were 4.3 points for the total score and ranged from 1.6 to 2.4 points for the domain scores. Coefficient alpha values were acceptable. Discussion: The self-administration version of the ALSFRS-R demonstrates high reproducibility and can be used in apps and online portals for both individual comparisons, facilitating the management of clinical care and group comparisons in clinical trials.